Epitopes prediction of PfEMP1-DBL2? recombinant protein from Indonesian Plasmodium falciparum Isolate for malaria vaccine development (Medico Legal Update, 2020)
The development of an effective vaccine against malaria is essential. Domain Duffy-binding-like (DBL)2?in Plasmodium falciparum erythrocyte membrane protein 1 (PfEMP1) protein is one of the vaccinecandidate proteins because of its binding capacity to ICAM-1 receptor. However, the high polymorphismneeds epitope identification before formulating a peptide-based vaccine. This study aimed to identify theconserved epitopes in PfEMP1-DBL2? by an immunoinformatic approach. The protein sequences wereanalyzed to predict the hydrophobicity attributes, T-cell and B-cell epitopes. T-cell epitopes were identifiedusing the NetCTL and Propred server and analyzed for population coverage rate using the IEDB analysistool. Moreover, the Bepipred 2.0 and Kolaskar Tangaonkar method combined with the K-means clusteringwere used to predict the B-cell epitopes. This study found that the hydrophobicity value of PfEMP1-DBL2?recombinant protein is 32.62, indicating that this protein is soluble and potentially fit into HLA alleles activesite. Two conserved antigenic CTL epitopes with near 90% population coverage rate in the malaria targetpopulation were identified. For Th cell epitopes, the NN-align algorithm showed no overlapping strongbinding epitope positions for three chosen Indonesian and African alleles. Three B-cell conserved epitopeswere identified at the position of 77-89, 236-254 and 360-377 amino acids with one cluster overlapping withICAM-1 determinant binding area. The predicted conserved epitopes within the protein in this study arevaluable in constructing a subunit peptide-based malaria vaccine candidate. A further experimental study isneeded to validate this approach as the next step in vaccine development.